Studi Numerik Pengaruh Variasi Rasio Diameter Silinder Sirkular Terhadap Performa Turbin Angin Savonius Overlap - Yuanditma Pranaja Kastara M; Emie Santoso; Priyo Agus Setiawan (Proceedings Conference on Marine Engineering and its Application, 2023)
- Experimental research on the performance of savonius wind turbine has been carried outwith additional overlap ratios and various diameter ratio of circular cylinder in front of returningblade. The validation of experimental results can be displayed by making numerical study researchwith Computational Fluid Dynamics (CFD) method. This method can also be used to obtaincoefficient of power. Numerical studies were conducted using savonius wind turbines with 0,3 overlapratio and also 0,4 meter of diameter and height. The various of circular cylinder diameter is ds/D =0,3; 0,4; 0,5; and 0,6. The wind speed is set at 5 m/s. The highest increase of performance savoniusoverlap wind turbines is 3,51% in the variations of ds/D = 0,4 to savonius overlap wind turbineswithout circular cylinder with 0,324 coefficient of power (Cp) at Tip Speed Ratio 1.